Canadian Interpretation and Construction of Maritime Conventions - Tetley, William (Revue générale de droit, 1991)
In this article, the author first describes the essentially civilian nature and origin of maritime law in the United Kingdom, the United States and Canada, a point unfortunately overlooked in the Supreme Court of Canada’s decision in the Buenos Aires Maru case [1986] 1 S.C.R. 752, but recognized in the judgement of the same Court in Chartwell Shipping Ltd v. Q.N.S. Paper, [1989] 2 S.C.R. 683.The article touches briefly on the federal jurisdiction over maritime law in Canada, the dual jurisdiction of the Federal Court and the superior courts of the provinces in maritime matters and the mixed civilian / common law system in Quebec.Consideration is then given to the Constitution Act, 1867, as interpreted by the much-criticized Labour Conventions decision of the Privy Council [1937] A.C. 326. The decision held that although the power to conclude international treaties and conventions in Canada is vested in the federal government alone, the enactment of the domestic legislation required to secure the implementation of such international agreements is not an exclusively federal matter, but may be a question of either federal or provincial competence, depending on the subject matter of the treaty or convention concerned.The author then reviews the principal rules of statutory interpretation which are provided for by the Vienna Convention on the Law of Treaties of 1969. He points out that, notwithstanding Canada’s ratification of this Convention in 1970, Canadian courts still tend to apply traditional (and often narrow) techniques of statutory interpretation when called upon to construe treaty texts, rather than keeping the goals of the agreement and intent of the parties in view, as the Vienna Convention requires. He indicates, however, a more recent judicial trend towards a more liberal methodology, as evidenced in decisions like R. v. Palacios, (1984) 45 O.R. (2d) 269 (Ont. C.A.)The article concludes with a brief overview of the major statutory interpretation rules applied by Canadian courts in construing local laws and international agreements and some aids to such interpretation. Professor Tetley, as a last tribute, applauds what he sees to be the slowly emerging "general consensus" on statutory and treaty interpretation in Canada.